The universal condemnation on the practice of riba = Pengutukan universal terhadap pengamalan riba - Mohamed Iqbal, Mohamed Ashraf; Ali, Mohammed Farid (IIUM Press, International Islamic University Malaysia, 2018)
The purpose of this paper is to examine the notion of riba. Riba is the only transgression in the Quran which invokes war on Allah SWT and his Messenger SAW. This writeup examines riba with a threefold objective: i) to establish that riba is a universal prohibition and not just an Islamic injunction, ii) to understand that riba was a widely entrenched practice during the time of the Prophet SAW, and that the abolishment of riba was done in stages according to the revelation of the Quran and, iii) to explain why riba is so detrimental to society. ******************************************************** Tujuan kertas ini adalah untuk melihat pendapat riba. Riba adalah satu-satunya pelanggaran dalam Qur’an yang memakan perang terhadap Allah SWT dan Rasulullah SAW. Penulisan ini mengkaji riba dengan tujuan tiga kali: i) untuk menetapkan riba itu adalah suatu larangan sejagat dan bukan sekadar injunksi Islam, ii) memahami bahawa riba adalah amalan yang luas di masa Nabi SAW, dan pemansuhan riba dilakukan secara berperingkat mengikut wahyu Al-Quran dan, iii) untuk menjelaskan mengapa riba sangat memudaratkan masyarakat.